Tourism - Robinson, Peter (Boston CAB International, 2020)
Tourism is becoming an increasingly important component of the global economy, and is subsequently a growing area of university study and research around the world. This unique new textbook covers all aspects of tourism from a contemporary perspective. It includes a range of theoretical and research-based topics supported by examples, case studies and comment boxes from industry representatives.The book is written to complement current teaching practices around the world, offering full coverage of all aspects of tourism management. These include infrastructure management, economic development, types of tourism, marketing, destination management and the 'pure theory' aspects of tourism as seen through sociology and tourist behaviour. As tourism is often studied alongside events, hospitality and leisure, these subjects are also included and used to draw together the major themes within tourism.
Includes bibliographical references and index.
Keywords: Tourism